A Dive Into Manually Picked Seafood Distributing Warehouse Optimization An investigation of how to create more efficient manual picking processes in seafood distributing warehouses - Widlöf, Matilda; Oresten, Tryggve (My University, 2023)
Seafood distributing warehouses struggle with low efficiency. It is an industry where historically low focus has been placed on developing the warehouses capabilities meaning that they have typically lagged behind other industries. There exists plentiful literature on the best practice of designing ware- houses but none which tries to adapt the best practice to the particular circumstances of the seafood distributing industry, a gap this study aims to bridge. Through an abductive case study focusing on theory elaboration the specific context was understood. Literature was used to find the best tools to use for the setting and in the case of storage assignment strategy simulations were utilized in order to evaluate the best technique. The results of this thesis indicate best ways of designing warehouses when it comes to their shape, layout, batching method, zoning methodology, choice of pallet racks and storage location assignment method for article placement. Of special interest is the best storage location assignment method found by the study which solely utilized frequency of demand for allocating storage spaces, though there exist methods this study did not attempt which might be superior. The study investigated cluster based models incorporating association into the model but these were shown to be subpar. Practical consequences of implementing the guidelines presented by this study include a more resource efficient manually picked seafood distributing warehouse with shorter lead times and more efficient storage.